Analysis of Free Indirect Discourse Narratives in the Works of Austen, Joyce, and Kingston - Manggong, Lestari (Journal of Language and Literature, 2017)
Language, with the complexity of its structure, can be problematic in terms of interpreting works of literature. This essay discusses the problems perceived in the process of interpretation of free indirect discourse narratives in Jane Austen’s Pride and Prejudice and Emma, James Joyce’s A Portrait of an Artist as a Young Man and The Dead, and Maxine Hong Kingston’s Tripmaster Monkey. Narratives with free indirect discourse opens up possibility of misinterpretation caused by the misconception of whose point of view the story is told. By looking at the works within the concept of narratology by Chatman (1978) and Prince (2003), such narratives—which apply the viewpoint of omniscient narrators—cause ambiguity to the voice of external and internal focalisers. This is due to the fact that the use of such narratives blends the two types of focalisations. The findings of this research lead to an argument that through external focalisation, the view becomes objective. Yet through internal focalisation, the view tends to become subjective as it is infiltrated by the character’s view. Such an argument then gives way to a conclusion that narratives with free indirect discourse gives effect to irony in the story-telling process of the works discussed. Keywords: free indirect discourse, narratology, focalisation